2011
DOI: 10.1002/ejoc.201101078
|View full text |Cite
|
Sign up to set email alerts
|

Olefin‐Metathesis‐Based Synthesis of Furans by an RCM/Deprotonation/Phosphorylation Sequence and Their Diels–Alder Reactions

Abstract: Butenolides, obtained by ring‐closing metathesis (RCM) of acrylates, undergo quantitative deprotonation with amide bases. Trapping of the resulting anions with electrophiles, for example, chlorophosphates, give furans. Subsequent Diels–Alder reaction and acid‐catalysed rearrangement of the resulting oxabicyclonorbornadienes give substituted benzenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…For practical purposes, we aimed at the development of a one-flask sequence to avoid isolation and purification of the RCM product. The removal of highly colored Ru residues from olefin metathesis reactions by distillation or chromatography is often a serious problem, [44] and we knew from previous work [45][46][47] that this is particularly true for the metathesis-based synthesis of unsaturated lactones due to their high polarity. Furthermore, for operational simplicity, a one-flask sequence should ideally proceed without exchange or removal of solvents, simply by addition of the appropriate catalysts and reagents at the appropriate time.…”
Section: Preliminary Considerationsmentioning
confidence: 99%
“…For practical purposes, we aimed at the development of a one-flask sequence to avoid isolation and purification of the RCM product. The removal of highly colored Ru residues from olefin metathesis reactions by distillation or chromatography is often a serious problem, [44] and we knew from previous work [45][46][47] that this is particularly true for the metathesis-based synthesis of unsaturated lactones due to their high polarity. Furthermore, for operational simplicity, a one-flask sequence should ideally proceed without exchange or removal of solvents, simply by addition of the appropriate catalysts and reagents at the appropriate time.…”
Section: Preliminary Considerationsmentioning
confidence: 99%
“…A simple access to furans is via the corresponding butenolides, which are formed easily by RCM [41]. This has been exploited by the Schmidt group, who showed that the extended enolate, formed by deprotonation of 20 with NaHMDS or LDA, can be O-phosphorylated or O-acetylated to provide the target furans in moderate to good yield (Scheme 10) [42]. Here, heteroaromaticity is achieved via transfer of the unsaturation from the carbonyl group to the ring system of the furan product.…”
Section: Synthesis Of Furans and Pyrroles By Rcm-isomerisation Sequencesmentioning
confidence: 98%
“…Here, heteroaromaticity is achieved via transfer of the unsaturation from the carbonyl group to the ring system of the furan product. The resulting adducts are useful as substrates for Diels-Alder reactions [42]. RCM-isomerisation approaches to pyrroles are rare (Scheme 11).…”
Section: Synthesis Of Furans and Pyrroles By Rcm-isomerisation Sequencesmentioning
confidence: 99%
“…Specifically, efficient RCM reaction of allyl acrylates 2-460 provided lactones 2-461 that were subsequently transformed into the corresponding phosphatyloxy furans 2-462 using O-phosphatylation reaction (Scheme 130). 228 …”
Section: Synthesis Of Furansmentioning
confidence: 99%